2016
DOI: 10.1038/srep26736
|View full text |Cite
|
Sign up to set email alerts
|

CuO-Decorated ZnO Hierarchical Nanostructures as Efficient and Established Sensing Materials for H2S Gas Sensors

Abstract: Highly sensitive hydrogen sulfide (H2S) gas sensors were developed from CuO-decorated ZnO semiconducting hierarchical nanostructures. The ZnO hierarchical nanostructure was fabricated by an electrospinning method following hydrothermal and heat treatment. CuO decoration of ZnO hierarchical structures was carried out by a wet method. The H2S gas-sensing properties were examined at different working temperatures using various quantities of CuO as the variable. CuO decoration of the ZnO hierarchical structure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(75 citation statements)
references
References 52 publications
2
73
0
Order By: Relevance
“…The detection mechanism consists of the strong electronic sensitization brought about by the copper oxides, which sulfurize to CuS or Cu 2 S upon exposure to H 2 S. In contrast to copper oxides, which are p -type semiconductors, copper sulfides are metallic and, therefore, exposure to H 2 S results in a dramatic increase in conductivity of the p-n nanomaterial. Furthermore, this sulfurization process is reversible, i.e., copper oxides are regenerated upon cleaning with air, which makes this approach very interesting for the chemoresistive sensing of H 2 S. Employing this approach, the detection of hydrogen sulfide in a wide concentration range has been reported (200 ppb to 1500 ppm) with a lower detection limit of about 20 ppb [35,36,37,38,39,40,41,42,43,44,45,46,47,52]. The best response and recovery times reported are units and tens of seconds, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection mechanism consists of the strong electronic sensitization brought about by the copper oxides, which sulfurize to CuS or Cu 2 S upon exposure to H 2 S. In contrast to copper oxides, which are p -type semiconductors, copper sulfides are metallic and, therefore, exposure to H 2 S results in a dramatic increase in conductivity of the p-n nanomaterial. Furthermore, this sulfurization process is reversible, i.e., copper oxides are regenerated upon cleaning with air, which makes this approach very interesting for the chemoresistive sensing of H 2 S. Employing this approach, the detection of hydrogen sulfide in a wide concentration range has been reported (200 ppb to 1500 ppm) with a lower detection limit of about 20 ppb [35,36,37,38,39,40,41,42,43,44,45,46,47,52]. The best response and recovery times reported are units and tens of seconds, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The selectivity in the detection of hydrogen sulfide and the effect of ambient moisture are not reported in these initial studies. Since then, many authors have reported the use of p -type cuprous or cupric oxides onto n -type metal oxides for detecting H 2 S. These include CuO-SnO 2 [38,39,40,41,42], Cu 2 O-SnO 2 [43], CuO-ZnO [44,45], CuO-SnO 2 -ZnO [46], and Cu 2 O-WO 3 [47] nanocomposites. Most papers show that the optimal operating temperature lies in the range from 100 °C to 400 °C, however, a few examples are given on the room-temperature detection of hydrogen sulfide [40,43].…”
Section: Metal Oxide Nanomaterialsmentioning
confidence: 99%
“…Functionalization of ZnO with metal oxide nanoparticles has found a great interest in recent years for the formation of semiconductive heterostructures with advanced optical, catalytic and electronic properties . Several p‐type metal oxide NPs like copper oxide (CuO), nickel oxide (NiO) or cobalt oxide (Co 3 O 4 ) have been deposited on n‐type ZnO nanostructures to form p‐n junction based devices. Heterostructures between semiconductors with different majority carrier type strongly enhanced photocatalytic efficiency.…”
Section: Surface‐engineering Of Zno Nanostructures With Nanoparticlesmentioning
confidence: 99%
“…Due to the mixing of MOS and other materials, it formed a variety of the unique properties for sensing material, such as a change in conductance, improved surface catalytic property, increasing surface reaction sites, and producing a high porosity [12]. In addition, a formed contact potential at the interface between MOS and other nanostructured materials has also enhanced the sensing performance of a gas sensor [13,14].…”
Section: Introductionmentioning
confidence: 99%